Simultaneous analysis of cytokines and co-stimulatory molecules concentrations by ELISA technique andof probabilities of measurable concentrations of interleukins IL-2, IL-4, IL-5, IL-6, CXCL8 (IL-8), IL-10, IL-13 occurring in plasma of healthy blood donors - Klabusay Martin; Kohutova Viera; Coupek Petr; Nenickova Marie; Tesarova Eva (Hindawi Limited, 2006)
Background. The cytokine network remarkably influences homeostasis. There is not a complex analysis describing physiological values of soluble cytokines in healthy individuals. Methods. Authors used the ELISA method to detect soluble cytokines and costimulatory molecules simultaneously in the plasma of 30 blood donors. Results. Data are shown as (a range of concentrations; median) IL-2 (0-74.48 pg/mL; 0), IL-4 (0-65.18 pg/mL; 0), IL-5 (0-86.69 pg/mL; 0), IL-6 (0-73.17 pg/mL; 0), IL-8 (0-74.8 pg/mL; 0), IL-10 (0-12.6 pg/mL; 0), IL-13 (0-3.9 pg/mL; 0), sCD40L (0-3.5 ng/mL; 0), and TNF-α (0-67.6; 0). For the IL-6 receptor, the concentration was 75.89±35.83 ng/mL (average ± SD), sCD23 28.9±15.22 ng/mL, and TGFβ1 14.98±12.39 ng/mL. A special approach was taken for the analysis of values, which had median 0. A model for the probability of detectable level's occurrence for each interleukin was formulated with intervals of confidence. Conclusion. These results provide reference values for cytokine levels in the plasma of healthy individuals.